Pengembangan Media Papan Sistem Peredaran Darah Manusia (Pasperdam) untuk Meningkatkan Hasil Belajar pada Materi Sistem Peredaran Darah Manusia Kelas V Madrasah Ibtidaiyah - Siti Muallifah; Hanik Yuni Alfiyah; She Fira Azka Arifin (Mathematics Education Study Program, 2025)
This study aims to develop an innovative learning media called Pasperdam (Human Circulatory System Board) to improve student learning outcomes on the topic of the Human Circulatory System in fifth-grade Madrasah Ibtidaiyah. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Feasibility testing was conducted through validation by material and media experts, as well as limited trials in the classroom, resulting in an average score of 94.76%, indicating that this media is highly suitable for use. Effectiveness testing was carried out by comparing pretest and posttest results, showing an increase in the average score from 52.57 to 82.57. Statistical analysis using a t-test proved that this improvement was significant with a p-value < 0.05. Practicality testing through questionnaires given to teachers and students revealed that 88.45% of respondents stated that this media is practical and easy to use. The conclusion of this study is that Pasperdam is effective, feasible, and practical for improving student learning outcomes on the topic of the Human Circulatory System, and it has a significant impact on enhancing learning outcomes in Madrasah Ibtidaiyah.